Estudio de factibilidad para la creación de una empresa de transporte de personal para las haciendas bananeras del cantón Valencia año 2015. - Mena García, David Vicente (2015)
The business activity is to provide a shuttle to the banana plantation with added value, for it must create a business enterprise under the administrative guidelines that establish the best service for the fulfillment of the objectives. The vision is achieved in the medium term competitiveness and positioning with the shuttle in the canton Valencia, so get achieve sustained and sustainable business growth that allows us to absorb a significant percentage of participation in the local market. The mission to be a company that provides transportation service personnel whose job is to ensure our customers a high quality of service through a strategic location, adequate infrastructure and vehicles, competitive prices and excellent customer service, demonstrating the commitment by the company Garcitrans. Customers of the company are the people of the banana plantations the canton Valencia and surrounding areas, seeking an efficient and guaranteed service to transport your staff you did their estates or workspaces. Garcitrans work in Valencia Canton province of Los Ríos, which will have the relevant packaging, making a total investment of USD 220.375,19 is required. Total revenues for the first year is $ 95,040.00, net income for the first year is $ 41.562,03 NPV is $ 74.528,81 and the IRR is 17% being positive meaning that the project is viable.